AN ASSESSMENT OF THE PERFORMANCE OF MAIZE (Zea Mays L.) AS AFFECTED BY PALM OIL MILL EFFLUENTS IN ABRAKA, DELTA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
The study was carried out to investigate the possible toxic effect of palm oil mill effluents on maize at varying concentrations. 2kg of soil samples obtained from site II, Delta State University, Abraka was contaminated with different concentrations (25, 50, 75 and 100%) of palm oil processing effluent alongside the control which served as guide for the determination of the toxicity of palm oil processing effluents. The results showed that maize seeds sown in the control soil had 100% germination with germination sighted at the 4th day after planting. 100% germination rate was also recorded in 25% palm oil effluent contaminated soils with germination commencing at the 4th day after planting. 50% concentration showed 55.6% germination rate starting at 6 days after planting. 75% concentration showed 27.6% germination rate starting at day 6 after planting. 100% concentration showed no growth with 0% germination. The highest plant height with mean value of 4.54cm was recorded in the control. The least value of height across the different concentration was observed in the 75% soil contaminated with palm oil mill effluents with plant height of 1.91cm. Seeds sown in 100% POME recorded no growth. The highest leaf number with mean value of 1.71 was recorded in the control. The study showed that pH varied among the different concentration of palm oil mill effluent with a range of 4.06 to 4.34. The study showed that palm oil processing effluents have negative effects on the germination and growth of maize.
Keywords: Assessment; Performance; Maize; Palm oil mill effluents